1975
DOI: 10.1128/aac.7.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Production and Mode of Action of Lactocin 27: Bacteriocin from a Homofermentative Lactobacillus

Abstract: Lactobacillus helveticus strain LP27 produced a bacteriocin, lactocin 27 Bacteriocins are antibiotic-like proteinaceous substances synthesized by certain strains of bacteria and are active against closely related species. The colicins produced by Escherichia coli and other species of Enterobacteriaceae have been studied extensively (15, 17). The recent studies with colicins (E1, E2, E., and K) suggest that the colicins manifest their biochemical effect(s) by interacting with their target directly (1,2,3,4,16,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
68
0
8

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 20 publications
10
68
0
8
Order By: Relevance
“…A narrow inhibitory spectrum, proteinaceous nature, and bactericidal mode of action are typical characteristics of antimicrobial agents classified as *bacteriocins (23). Very few lactobacifli have been confirmed to produce true bacteriocins within these criteria (3,4,6,25,26). Only a single bacteriocin has been identified and characterized within the L. helveticus species.…”
mentioning
confidence: 99%
“…A narrow inhibitory spectrum, proteinaceous nature, and bactericidal mode of action are typical characteristics of antimicrobial agents classified as *bacteriocins (23). Very few lactobacifli have been confirmed to produce true bacteriocins within these criteria (3,4,6,25,26). Only a single bacteriocin has been identified and characterized within the L. helveticus species.…”
mentioning
confidence: 99%
“…Bacteriocin genes are typically plasmid borne (43), but the genetic determinants encoding helveticin J appear to reside on the chromosome (16). Evidence for chromosomally located bacteriocin genes has also been reported for lactacin B produced by Lactobacillus acidophilus N2 (2) and lactocin 27 produced by L. helveticus LS18 (44).…”
mentioning
confidence: 99%
“…Barefoot and Klaenhammer (4) reported that 63% of the Lactobacillus acidophilus strains they examined produced bacteriocins. Bacteriocins produced by L. acidophilus 11088, L. acidophilus N2, Lactobacillus helveticus 481, and L. helveticus LP27 have been purified and shown to constitute a heterogeneous class of antimicrobial peptides (5,25,33,42). Although efforts have been made to characterize the proteinaceous nature of these bacteriocins, limited information is available about the genetic determinants of bacteriocins from lactobacilli or other LAB.…”
mentioning
confidence: 99%